PENGARUH KEPEMIMPINAN DAN DUKUNGAN ANGGOTA TERHADAP PERAN SERIKAT PEKERJA PT. PLN PERSERO AREA TEGAL - Edwin Febriananda; Ari Pradhanawati; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
The role of workers union is affected by several factors, such as good leadership and a strong support from its members. This study aims to identify and explain the effect of leadership and members support on the role of workers union in the Workers union of PT. PLN Persero Area Tegal. This type of research is explanatory research. Techniques of data collection using interviews, questionnaires and observation. The conclusion from this study is that there is effect between leadership and members support on the role of workers unions in Workers union of PT. PLN Persero Area Tegal. Based on the conclusion that the union need to improve human resources, especially the increase in knowledge about the business organization for leaders to be better and there needs to be agreement in appreciation and attention to the work of union members to be comfortable so that workers union can obtain strong members support to improve the role of workers union.